Biopolymer-delivered vascular endothelial growth factor improves renal outcomes following revascularization - Guise, Erika (Am J Physiol Renal Physiol, 2019)
Renal angioplasty and stenting (PTRAs) resolves renal artery stenosis, but inconsistently improves renal function, possibly due to persistent parenchymal damage. We developed a bioengineered fusion of a drug delivery vector (elastin-like polypeptide, ELP) with vascular endothelial growth factor (VEGF), and showed its therapeutic efficacy. We tested the hypothesis that combined ELP-VEGF therapy with PTRAs improves renal recovery more efficiently than PTRAs alone, by protecting the stenotic renal parenchyma. Unilateral renovascular disease (RVD) was induced by renal artery stenosis in 14 pigs. Six weeks later, stenotic kidney blood flow (RBF) and glomerular filtration rate (GFR) were quantified in vivo using multidetector CT. Blood and urine were collected during in vivo studies. All pigs underwent PTRAs and then were randomized into single intrarenal ELP-VEGF administration or placebo (n = 7 each) groups. Pigs were observed for four additional weeks, in vivo CT studies were repeated, and then pigs were euthanized for ex vivo studies to quantify renal microvascular (MV) density, angiogenic factor expression, and morphometric analysis. Renal hemodynamics were similarly blunted in all RVD pigs. PTRAs resolved stenosis but modestly improved RBF and GFR. However, combined PTRAs+ ELP-VEGF improved RBF, GFR, regional perfusion, plasma creatinine, asymmetric dimethlyarginine (ADMA), and albuminuria compared with PTRAs alone, accompanied by improved angiogenic signaling, MV density, and renal fibrosis. Greater improvement of renal function via coadjuvant ELP-VEGF therapy may be driven by enhanced MV proliferation and repair, which ameliorates MV rarefaction and fibrogenic activity that PTRAs alone cannot offset. Thus, our study supports a novel strategy to boost renal recovery in RVD after PTRAs.